Theory of al- Istiṣlaḥ as the Istinbāt al-Ḥukmi Method on the MUI Fatwa - Yusuf, Maulana; Umar, Hasbi; Ulum, Bahrul; Badarussyamsi, Badarussyamsi (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article presents a theoretical study of Istiṣlaḥ and also its application to the MUI fatwa of Jambi Province. The four fatwas studied include; fatwas about religious lectures, the bride and groom sitting side by side at wedding receptions, friendship between Muslims and other people, and fatwas about the commemoration of Islamic holidays. The main problem studied is what is the position of Istiṣlaḥ and its application to the MUI fatwa of Jambi Province? This article comes from qualitative phenomenological research which examines the phenomenon of fatwa application using the Istiṣlaḥ paradigm on four cases that are the focus. The results of the research show that in implementing the fatwa with the application of the principles of al-Istiṣlaḥ, the Jambi MUI succeeded in getting out of its attachment to certain schools of jurisprudence. The use of fatwa using Istiṣlaḥ independently is not found in the uṣūl fiqh of the Syafi'i school, nor in the practice of its fiqh issues, while the MUI fatwa uses it. The MUI fatwa continues to follow the patterns and manhaj outlined by sectarian scholars, even though it does not limit itself to certain sects. Artikel ini menyajikan kajian teoretis Istiṣlaḥ dan juga penerapannya pada fatwa MUI Provinsi Jambi. Empat fatwa yang dikaji antara lain; fatwa tentang ceramah agama, pengantin yang duduk bersanding dalam resepsi pernikahan, silaturahmi Umat Islam dengan umat lain, dan fatwa tentang peringatan Hari- hari Besar Islam. Permasalahan utama yang dikaji adalah bagaimana kedudukan Istiṣlaḥ dan aplikasinya pada fatwa MUI Provinsi Jambi? Artikel ini berasal dari penelitian kualitatif fenomenologis yang mengkaji fenomena aplikasi fatwa yang berparadigma Istiṣlaḥ terhadap empat kasus yang menjadi fokus. Hasil penelitian menunjukkan bahwa dalam penerapan fatwa dengan penerapan prinsip-prisip al- Istiṣlaḥ, MUI Jambi berhasil keluar dari keterikatan terhadap mazhab fiqih tertentu. Penggunaan fatwa dengan menggunakan Istiṣlaḥ secara mandiri tidak ditemukan dalam uṣūl fiqh mazhab Syafi’i, pun dalam praktik masalah fiqihnya, sementara fatwa MUI memakainya. Fatwa MUI tetap mengikuti pola dan manhaj yang digariskan para ulama mazhab, sekalipun tidak membatasi diri pada mazhab tertentu.